Donor selection for KIR alloreactivity is associated with superior survival in haploidentical transplant with PTCy - Zou, Jun; Kongtim, Piyanuch; Srour, Samer A.; Greenbaum, Uri; Schetelig, Johannes; Heidenreich, Falk; Baldauf, Henning; Moore, Brandt; Saengboon, Supawee; Carmazzi, Yudith; Rondon, Gabriela; Ma, Qing; et al. (Frontiers in Immunology, 2022)
With the continuous increase in the use of haploidentical donors for transplantation, the selection of donors becomes increasingly important. Haploidentical donors have been selected primarily based on clinical characteristics, while the effects of killer cell immunoglobulin-like receptors (KIRs) on outcomes of haploidentical-hematopoietic stem cell transplantation (haplo-HSCT) with post-transplant cyclophosphamide (PTCy) remain inconclusive. The present study aimed to thoroughly evaluate the effect of KIRs and binding ligands assessed by various models, in addition to other patient/donor variables, on clinical outcomes in haplo-HSCT. In a cohort of 354 patients undergoing their first haplo-HSCT, we found that a higher Count Functional inhibitory KIR score (CF-iKIR) was associated with improved progression-free survival (adjusted hazard ratio [HR], 0.71; P = .029) and overall survival (OS) (HR, 0.66; P = .016), while none of the other models predicted for survival in these patients. Moreover, using exploratory classification and regression tree analysis, we found that donor age <58 years combined with cytomegalovirus-nonreactive recipient was associated with the best OS, whereas donor age >58 years was associated with the worst OS. In the rest of our cohort (80%), cytomegalovirus-reactive recipients with a donor <58 years old, a higher CF-iKIR was associated with superior OS. The 3-year OS rates were 73.9%, 54.1% (HR, 1.84; P = .044), 44.5% (HR, 2.01; P = .003), and 18.5% (HR, 5.44; P <.001) in the best, better, poor, and worse donor groups, respectively. Our results suggest that KIR alloreactivity assessed by CF-iKIR score can help optimize donor selection in haplo-HSCT.